Synergistic Biophysical Techniques Reveal Structural Mechanisms of Engineered Cationic Antimicrobial Peptides in Lipid Model Membranes - Heinrich, Frank (2020)
In the quest for new antibiotics, two novel engineered cationic antimicrobial peptides (eCAPs) have been rationally designed. WLBU2 and D8 (all 8 valines are the d-enantiomer) efficiently kill both Gram-negative and -positive bacteria, but WLBU2 is toxic and D8 nontoxic to eukaryotic cells. We explore protein secondary structure, location of peptides in six lipid model membranes, changes in membrane structure and pore evidence. We suggest that protein secondary structure is not a critical determinant of bactericidal activity, but that membrane thinning and dual location of WLBU2 and D8 in the membrane headgroup and hydrocarbon region may be important. While neither peptide thins the Gram-negative lipopolysaccharide outer membrane model, both locate deep into its hydrocarbon region where they are primed for self-promoted uptake into the periplasm. The partially α-helical secondary structure of WLBU2 in a red blood cell (RBC) membrane model containing 50 % cholesterol, could play a role in destabilizing this RBC membrane model causing pore formation that is not observed with the D8 random coil, which correlates with RBC hemolysis caused by WLBU2 but not by D8.